2005
DOI: 10.1136/bjsm.2004.012336
|View full text |Cite
|
Sign up to set email alerts
|

Diffusely increased bone scintigraphic uptake in patellofemoral pain syndrome

Abstract: Objectives: Painful disorders of the patellofemoral joint are one of the most frequent complaints in orthopaedic and sports medicine. The aims of this study were to determine whether bone scintigrams of patients suffering from patellofemoral pain syndrome (PFPS) show diffuse uptake and in what bony compartment of the knee uptake, if any, was localised. Methods: Fifty eight patients with chronic PFPS were examined. All patients underwent a detailed clinical history and a thorough physical examination of the kne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 34 publications
(22 reference statements)
1
41
0
2
Order By: Relevance
“…Recently, imaging data from patients with PFP have been published using newer imaging modalities and technologies in hope that these modalities are more sensitive to detect any possible pathology related to the cartilage under the patella and in the patellar groove. Positron emission tomography-computed tomography (PET-CT) imaging shows that 44-85 % of older adults (mean age [29][30][31][32][33][34] with PFP show increased tracer uptake in the patellofemoral joint that tends to coincide with bone marrow oedema, subchondral bone cysts, and cartilage damage [45][46][47]. Furthermore, there appears to be an association between the tracer uptake and pain intensity, and an association between pain location and location of tracer uptake that suggests an aetiological link [46].…”
Section: Patellofemoral Pain and Pathology?mentioning
confidence: 99%
“…Recently, imaging data from patients with PFP have been published using newer imaging modalities and technologies in hope that these modalities are more sensitive to detect any possible pathology related to the cartilage under the patella and in the patellar groove. Positron emission tomography-computed tomography (PET-CT) imaging shows that 44-85 % of older adults (mean age [29][30][31][32][33][34] with PFP show increased tracer uptake in the patellofemoral joint that tends to coincide with bone marrow oedema, subchondral bone cysts, and cartilage damage [45][46][47]. Furthermore, there appears to be an association between the tracer uptake and pain intensity, and an association between pain location and location of tracer uptake that suggests an aetiological link [46].…”
Section: Patellofemoral Pain and Pathology?mentioning
confidence: 99%
“…Excessive knee valgus from hip adduction (movement of the femur relative to the pelvis) increases the Q-angle because it displaces P atellofemoral pain syndrome (PFPS) is a common problem experienced by active adults and adolescents 31 ; however, its etiology has remained vague and controversial. 22 Unlike other knee dysfunctions (eg, anterior cruciate ligament injury), which often have a specific onset and mechanism of injury, patients with PFPS generally report diffuse peripatellar and retropatellar pain of an insidious onset. Dye 9 has described PFPS as an orthopedic " the patella medially relative to the tibial tubercle.…”
mentioning
confidence: 99%
“…Additionally, an association between restoration to normality of the bone scan and the resolution of AKP after conservative treatment has also been documented 18. Näslund et al 47 found that nearly 50% of patients with AKP show a diffuse uptake in the scintigraphy in one or more of the bony compartments of the knee joint.…”
Section: Diagnosismentioning
confidence: 90%